1226 A MULTI-DISCIPLINARY APPROACH TO TRANSFORMING EYE CARE SERVICES FOR CARE HOME RESIDENTS. (16th January 2023) - Ma, N; Low, S; Hasan, S; Lawal, A; Patel, S; Nurse, K; McNaughton, G; Aggarwal, R; Evans, J; Koria, R; Lam, C; Chakravorty, M; et al.
Abstract: Introduction: Care home residents can have variable access to eye care services and treatments. We developed a collaborative approach between optometrists, care homes, and primary and secondary care to enable personalised patient-centred care. Objective: To develop and evaluate an integrated model of eye care for care home residents. Methods: Small scale plan-do-study-act (PDSA) service tests were completed in three care-homes in Southwark (2 residential, 1 nursing) between November 2021 to May 2022. Processes were compared to historical feedback and hospital-based ophthalmology clinic attendances (Mar 2019-2020). Hospital-like assessments were piloted at two care homes for feasibility and acceptability. Further piloting utilised usual domiciliary optometry-led assessment with multidisciplinary meeting access (including optometrist, GP, geriatrician, ophthalmologist and care home nurse) to reduce duplication of assessments and to evaluate MDM processes and referral rates. Results: Examination was 100% successful at home (visual acuity and pressure measurement) compared to hospital outpatients (71.7% success visual acuity, 54.5% pressures). Examination was faster than in hospital settings (16 minutes vs 45 minutes-1 hour). Residents were away from usual activities for 32 minutes vs 6 hours for hospital visits including transport. Residents were less distressed with home-based assessments. Did-Not-Attend (DNA) rates reduced (26.7% to 0%), secondary care discharge rates improved (8.4% to 32%). Hospital eye service referral were indicated in 19% -23%, half of which were for consideration of cataract surgery. Alternative conservative plans were agreed at MDM for nursing home residents who were clinically too frail or would not have been able to comply with treatments avoiding 33% unnecessary referrals. Conclusions: Home-based eye care assessments appear better tolerated and are more efficient for residents, health and care staff. Utilising an MDM for optometrists to discuss residents with ophthalmologists and wider MDT members enabled personalised patient-centred decision-making. Future work to test this borough wide is in progress.